Formation of aroma compounds by degradation of beta-carotene from crude palm oil and oil palm wastes - Suria, Kupan (2016)
Aroma compounds such as α-ionone, β-ionone, β-damascenone and other important compounds can be produced via degradation of carotenoids. Extraction of natural carotenoid-derived aroma compounds directly from natural sources is expensive and uneconomical because isolation of single pure natural aroma compounds directly from plant sources are difficult and involves tedious work as it is available in a very low yield. Therefore, this research aims to produce aroma compounds by degradation of β-carotene from crude palm oil (CPO) and oil palm wastes (OPW). Palm carotene extraction process was performed by using soxhlet adsorption. The extraction process mainly aimed at extracting β-carotene high in concentration and yield. Based on the optimization of this extraction technique, soxhlet adsorption recovered highest concentration of β-carotene at 1:4 ratio of CPO: HP-20 for 1 hour isopropanol (IPA) extraction time. The concentration of β-carotene extracted was determined by using HPLC and UV-Vis standard calibration curve. CPO showed highest concentration of β-carotene under the optimised conditions which was 3770 ppm, followed by palm pressed fiber (PPF), with concentration of 1397 ppm and empty fruit bunch (EFB) yielded lowest concentration of 687 ppm. As for production of aroma compounds, optimization of degradation reaction conducted using commercial β-carotene in order to achieve optimum degradation conditions. Different sonication time, reaction time and reaction temperature was studied to ascertain the optimization of thermal degradation reaction. Effect of sonication, light and amount of sample also catalyst was studied to optimize the oxidative degradation. Based on the results obtained, the optimum condition for thermal degradation is 1 hour sonication, 5 hours of reaction and 120-130°C. Whereas for oxidative degradation vial must be completely covered, sealed and kept at room temperature. The extracted palm carotene further was degraded using thermal and oxidative degradation under optimized reaction conditions. The oxidative degradation using extracted carotene failed to produce any aroma compounds. However, thermal degradation of extracted β-carotene from both CPO and OPW produced aroma compounds such as β-ionone, dihydroactinidiolide (DHA), D-limonene, β-ionone epoxide and 3-oxo-β-ionone. The major aroma compound with highest composition produced is DHA (45.91 %) followed by β-ionone which was analysed using GC-MS and GC-FID. Overall, this research signifies that, recovery of β-carotene by soxhlet adsorption from CPO is higher in concentration compared to OPW. Thermal degradation method is a more advantageous technique for production of aroma compounds compared to oxidative degradation. The results obtained prove that production of aroma compounds by degradation of β-carotene from CPO and OPW is viable.